2010
DOI: 10.1108/13664381011087506
|View full text |Cite
|
Sign up to set email alerts
|

Social infrastructure partnerships: a firm rock in a storm?

Abstract: Purpose-The purpose of this paper is to use the example of public housing renewal public-private partnerships (PPPs) to build knowledge on whether social infrastructure PPPs may appeal to the private sector as a less risky investment in a time of global financial uncertainty. Design/methodology/approach-The research is based on an international literature review and a limited number of semi-structured interviews with social housing PPP participants in England, the USA and Australia. These interviews were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…On the other hand, other researchers are showing that there is no significant influence of infrastructure on improving the quality of human resources. They revealed that the cause of these conditions was limited government resources (Monteiro & Turnovsky, 2008), lack of trust from policymakers (Qureshi, 2009), economic conditions such as recession (Gilmour, et al, 2010) and structural barriers to infrastructure (Freed, et al, 2013;Gupta, et al, 2014;Pulok, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other researchers are showing that there is no significant influence of infrastructure on improving the quality of human resources. They revealed that the cause of these conditions was limited government resources (Monteiro & Turnovsky, 2008), lack of trust from policymakers (Qureshi, 2009), economic conditions such as recession (Gilmour, et al, 2010) and structural barriers to infrastructure (Freed, et al, 2013;Gupta, et al, 2014;Pulok, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To expand the scope and improve the efficiency of PPP mechanisms in Russian regions, it may be useful to study the foreign experience of using such financing schemes in infrastructure development. For example, in Australia, 10-15% of total investment in infrastructure by the mid-2000s was carried out at the expense of public-private partnerships (Gilmour et al, 2010).…”
Section: Figure 1 Distribution Of Russian Regions Based On Dynamic Imentioning
confidence: 99%
“…In this regard, economic infrastructure and social infrastructure have consequently emerged. Although both economic and social infrastructures have significant social impacts on individuals, communities, and the general public at large in terms of practicality, a distinction between both infrastructures based on their social impact is ambiguous and difficult to establish (Gilmour et al, 2010). Likewise, SIP is services delivered by welfare agencies, more commonly known as "human services".…”
Section: Social Infrastructurementioning
confidence: 99%
“…Previous studies have focused mainly on examining the SIP within the PPP contracting method (Jefferies, 2006;Jefferies, and McGeorge, 2008;Jefferies and McGeorge, 2009;Syuhaida and Aminah, 2009;Hellowell and Pollack, 2011;Gilmour et al, 2010). PPP is the wider term used to indicate the specific partnership between public and private sector.…”
Section: Social Infrastructurementioning
confidence: 99%
See 1 more Smart Citation